Crush eaudiobook A novel. - Calhoun, Ada (Books on Tape, 2025)
A Today Show, New Yorker, Washington Post , New York Times , TIME, Harper's Bazaar , Town & Country , Bustle, Lit Hub, Zibby Owens , Marie Claire , AARP, Bloomberg, The Millions , The Seattle Times and Vulture Most Anticipated Book “Ada Calhoun writes with absolute clarity about the giddiest and most destabilizing feeling—the crush. This novel made me feel dizzy and I loved every second. Calhoun can seduce me any day of the week.” —Emma Straub, New York Times bestselling author of This Time Tomorrow When a husband asks his wife to consider what might be missing from their marriage, what follows surprises them both—sex, heartbreak and heart rekindling, and a rediscovered sense of all that is possible She’s happy and settled and productive and content in her full life—a child, a career, an admirable marriage, deep friendships, happy parents, and a spouse she still loves. But when her husband urges her to address what the narrow labels of “husband” and “wife” force them to edit out of their lives, the very best kind of hell breaks loose. Using the author’s personal experiences as a jumping-off point, Crush is about the danger and liberation of chasing desire, the havoc it can wreak, and most of all the clear sense of self one finds when the storm passes. Destined to become a classic novel of marriage, and tackling the big questions being asked about partnership in postpandemic relationships, Crush is a sharp, funny, seductive, and revelatory novel about holding on to everything it’s possible to love—friends, children, parents, passion, lovers, husbands, all of the world’s good books, and most of all one’s own deep sense of purpose.